2019
DOI: 10.1111/apt.15087
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: non‐alcoholic fatty liver disease is associated with a history of osteoporotic fractures but not with low bone mineral density

Abstract: Summary Background Several studies have explored the effect of non‐alcoholic fatty liver disease (NAFLD) on bone mineral density (BMD) and risk of osteoporotic fractures in adults. However, the extent to which NAFLD adversely affects bone health remains uncertain. Aim To provide a quantitative estimation of the magnitude of the association of NAFLD with BMD or history of osteoporotic fractures in adults. Methods We searched PubMed, Web of Science, and Scopus using predefined keywords to identify all observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 52 publications
3
45
1
Order By: Relevance
“…However, unlike adult individuals in whom the bone volume does not change over time, a child's bones grow and model over time, with the growth of individual bones not occurring uniformly in three dimensions. It is also noteworthy that sufficient population‐based data correlating BMD measures with fracture risk in healthy children and adolescents are unavailable . Currently, lifestyle modifications to improve diet and increase physical activity are recommended as the first‐line treatment for all children and adolescents with NAFLD .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, unlike adult individuals in whom the bone volume does not change over time, a child's bones grow and model over time, with the growth of individual bones not occurring uniformly in three dimensions. It is also noteworthy that sufficient population‐based data correlating BMD measures with fracture risk in healthy children and adolescents are unavailable . Currently, lifestyle modifications to improve diet and increase physical activity are recommended as the first‐line treatment for all children and adolescents with NAFLD .…”
Section: Discussionmentioning
confidence: 99%
“…Second, although there is a relatively low heterogeneity in the pooled primary analysis ( I 2 = 55.5%), the sample size of the meta‐analysis is relatively small (n = 625), and the overall quality of the included studies is not consistently high (with a medium to high risk of bias according to the NOS of the available studies as shown in Supporting Tables ). Third, most of the eligible studies have reported incomplete adjustments for established risk factors for low BMD (such as physical activity, pubertal stage, serum 25‐hydroxyvitamin D 3 concentrations, or vitamin D/calcium intakes), especially during the late childhood and peripubertal years, which is a critical period for bone accretion . In particular, we believe that the lack of data on serum vitamin D 3 concentrations or vitamin D supplementation is one of the most important weaknesses of the included studies, given that low vitamin D 3 is a risk factor for osteomalacia and osteoporosis both in adults and in adolescents .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although initially recognized as being primarily as a hepatic disorder, NAFLD is now known to affect multiple organs in the body such as the heart, kidneys and endocrine organs, and is a major risk factor in chronic diseases affecting these organs [5][6][7][8]. More pertinently, NAFLD is now recognized as the hepatic manifestation of metabolic syndrome with the majority of NALFD patients having some, if not all, features of this syndrome [2,9,10].…”
Section: Introductionmentioning
confidence: 99%